Embedded electronic circuits for cryptography, hardware security and true random number generation: an overview. (13th December 2016) - Acosta, Antonio J.; Addabbo, Tommaso; Tena‐Sánchez, Erica
Summary: We provide an overview of selected crypto‐hardware devices, with a special reference to the lightweight electronic implementation of encryption/decryption schemes, hash functions, and true random number generators. In detail, we discuss the hardware implementation of the chief algorithms used in private‐key cryptography, public‐key cryptography, and hash functions, discussing some important security issues in electronic crypto‐devices, related to side‐channel attacks (SCAs), fault injection attacks, and the corresponding design countermeasures that can be taken. Finally, we present an overview about the hardware implementation of true random number generators, discussing the chief electronic sources of randomness and the types of post‐processing techniques used to improve the statistical characteristics of the generated random sequences. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We provide an overview of selected crypto‐hardware devices, with a special reference to the lightweight electronic implementation of encryption/decryption schemes, hash functions, and true random number generators. In detail, we discuss the hardware implementation of the chief algorithms used in private‐key cryptography, public‐key cryptography, and hash functions, discussing some important security issues in electronic crypto‐devices, related to side‐channel attacks, fault injection attacks, and the corresponding design countermeasures that can be taken. Finally, we present an overview about the hardware implementation of true random number generators, discussing the chief electronic sources of randomness and the types of post‐processing techniques used to improve the statistical characteristics of the generated random sequences.